Product and Market Observations on Furniture Technological Developments - Nirmal, Umar; Kiat Ng, Poh; Siong Jee, Kian; Anton, Eric (International Journal of Engineering and Technology, 2018)
The purpose of this study was to identify ergonomics aspects, traits and flaws in furniture designs and forecast the future advancements of furniture technology. A market and product analysis were conducted in order to identify technological patterns in furniture design. Based on observations of these furniture designs, recommendations on future developments and advancements are suggested for improved functionality and comfortability in furniture technology. The findings suggested that aspects such as user-centred design, modularity, soft close technology, space-saving awareness, usability awareness and sustainability were among the key ergonomics aspects that designers should emphasise on for the future advancements of furniture technology. This study contributes to the understanding on combinations of consumer preferences, furniture market trends and technological advancements towards creating an indication of how furniture can be designed to adapt with the equivocal change in the furniture market.Â